2008
DOI: 10.2304/ciec.2008.9.4.354
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers' Critical Reflections of Arts and Education Discourse: Reconstructions of Experiences in Early Childhood and Higher Education

Abstract: This layered account of arts education is produced through the three authors' critical reflections of experiences in their own early childhood education, and their pre-service teacher education. The first layer establishes links between the arts, learning in the arts and critically reflective practices through an account of teaching and learning in Unit X -a compulsory arts unit in a four-year teacher education course. The second layer is a recall of early childhood arts experiences and how these informed our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The number and average of courses that combine theory with practice using mixed modes of instruction is also deemed to be insufficient. It seems that in all of the departments of education the arts education provided lacked courses on arts pedagogy and the courses offered were more theory-based and less school-centered than they should be, as previous studies had shown (Miller et al, 2008;Sotiropoulou et al, 2010;Stavrou, 2009). What possibly lies behind these findings is the outdated view that the arts are a discrete discipline within a curriculum, one that cannot or need not be integrated into the school learning process and life, as recent studies have shown that they should be (Amadio et al, 2006;Burnaford et al, 2007;Catterall, 2002;Deasy, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and average of courses that combine theory with practice using mixed modes of instruction is also deemed to be insufficient. It seems that in all of the departments of education the arts education provided lacked courses on arts pedagogy and the courses offered were more theory-based and less school-centered than they should be, as previous studies had shown (Miller et al, 2008;Sotiropoulou et al, 2010;Stavrou, 2009). What possibly lies behind these findings is the outdated view that the arts are a discrete discipline within a curriculum, one that cannot or need not be integrated into the school learning process and life, as recent studies have shown that they should be (Amadio et al, 2006;Burnaford et al, 2007;Catterall, 2002;Deasy, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The orientations that arts courses could have as to the various aspects of arts education, such as creative, academic, productive, technical (McKaen, 2000;Miller et al, 2008) was examined in the third research question. Data were collected by looking into the objectives of every course and the instruction modes used.…”
Section: Data Collection and Analysis Processmentioning
confidence: 99%
“…In such a setting, children gain the ability to work together, listen to others' ideas, and jointly develop their own (Arabaci & Gok, 2021;Eglinton, 2003). Several fundamental elements of work, such as respecting and accepting the authenticity of others' work, can help children develop their artistic abilities (Garvis et al, 2012;Miller et al, 2008;Workman, 2017;Wright, 2003).…”
Section: The Role Of the Early Childhood Education And Care Teachermentioning
confidence: 99%
“…As Jalongo (1999) asserts, teachers who are not confident with their own artistic ability will negatively influence the art of their own students. By simply including art education as part of pre-service training and ongoing professional development, teachers will be given the opportunity to develop basic skills and reflect critically on their own practice to assist themselves in managing artistic learning at school (Miller et al, 2008). The implication for practice is that teachers should be provided with up-to-date research on how best to acknowledge and respect children's emotional investment in their own visual artwork.…”
Section: Challenging Adult Understandings Of Displaying Children's Armentioning
confidence: 99%